The Influence of Human Resource Development, Competence, and Teamwork on the Performance of Account Representative (AR) Employees at KPP Madya Surabaya - Khatami, Addienul; Rahayu, Sri; Sundjoto, Sundjoto; Fitrianty, Rifda (Transpublika Publisher, 2026)
Improving employee performance is critical for the Directorate General of Taxes (DGT), especially as it undergoes bureaucratic reform and service digitization. The Account Representative (AR) at the Surabaya Medium Tax Office (KPP Madya Surabaya) plays a vital frontline role in serving taxpayers and influencing national revenue. This research seeks to examine the extent to which Human Resource Development, Competence, and Teamwork shape the performance of Account Representative personnel at KPP Madya Surabaya. Employing a quantitative correlational approach, data were collected through a questionnaire that had undergone validity and reliability testing. The study involved 40 employees selected via a saturated sampling technique. Data analysis was conducted using multiple linear regression. The findings reveal that Human Resource Development and Competence do not exert a statistically significant influence on employee performance when assessed individually, whereas Teamwork demonstrates a significant partial effect. When evaluated collectively, all three independent variables significantly influence performance outcomes. The coefficient of determination (R²) of 0.588 indicates that Human Resource Development, Competence, and Teamwork collectively account for 58.8 percent of the variance in employee performance, with the remaining proportion attributable to factors beyond the scope of this research model. This study offers evidence-based recommendations for the DGT and Surabaya Medium Tax Office to design better-integrated HR policies, strengthen teamwork, and address competency gaps among Account Representatives, ultimately supporting reform, service quality, and revenue goals.